Fostering democratic engagement: factors shaping youth political participation in Kazakhstan - Baizhumakyzy, Zaure; Tangkish, Nazira; Mazhinbekov, Saken; Sarsenbekov, Zhandos; Korganova, Saipzhamal (Frontiers in Political Science, 2025)
This study aims to analyze the factors influencing youth political participation, focusing on the role of political culture, transforming youth activities, patriotism, and civic responsibility in the context of developing democracies. Using data collected from 350 young people across five major universities in the large cities of Kazakhstan, we employed structural equation modeling to test our hypotheses. The results reveal that political culture significantly influences political participation, and this relationship is strengthened by civic responsibility, but not by patriotic sentiment. Interestingly, while youth with strong democratic values actively participate in political processes, they prefer to work within existing institutional frameworks rather than engage in transformative activities. This study provides theoretical and practical recommendations for increasing political engagement among the youth in Kazakhstan. Unlike existing studies that focus on institutional forms of youth participation, this study is the first to systematically analyze the role of civic responsibility and patriotism and their links to political culture and political participation, which opens new perspectives for understanding the mechanisms of youth engagement in the political process in emerging democracies.